Shortage in general practice despite the feminisation of the medical workforce: a seeming paradox? A cohort study - Boode Beppie; Zee Jouke; Stevens Fred; Maiorova Tanja; Scherpbier Albert (BMC Health Services Research, 2008)
Abstract Background Female medical students often prefer primary care specialties, while male students appear to be attracted to hospital specialties. Notwithstanding the steady feminisation of medicine, in many countries there are still difficulties in recruiting trainees for general practice. This seeming paradox raises the question on what specific role gender plays in a specialty choice. The authors looked at the (a) the role of gender in general practice specialty choice of Dutch medical students, (b) the decisive factors in career choice and relation of gender to these, and (c) differences in how male and female students are influenced by the GP clerkship. Methods A cohort of 206 final year medical students at the Maastricht University, the Netherlands were asked to complete a questionnaire focusing on career preferences before and after a 12-week general practice clerkship and at graduation, a couple of months later. Results Gender was significantly related to willingness to become a GP in bivariate analysis. Adding variables in multivariate analysis made this effect disappear. While females expressed overall higher preference for general practice than males, after the GP clerkship likelihood of choosing general practice increased with 38% among male and 22% among female students. After graduation, interest in general practice had dropped, mainly among females. Attitudes predicting a GP career choice were: extrinsic career motivation before the clerkship, and the content of GP work (patient contacts, treatments) and motivation to work with chronic and palliative patients after the clerkship. Conclusion Gender 'as such' appeared not to be a distinctive predictor of specialty choice. It is students' attitudes towards GP work and preferred patient category that determine the career choice in general practice. However, more male students were positively influenced by the GP clerkship than female students. The motivating effect of the clerkship is not long lasting. Especially female graduates change their interest in favour of other specialties, which may explain why eventually few students choose general practice. It might be worthwhile to reinforce an initial preference for general practice by motivational guidance throughout the whole period of clerkships.